From chaos to order: optimizing fecal microbiota transplantation for enhanced immune checkpoint inhibitors efficacy - Anqi Lin; Aimin Jiang; Lihaoyun Huang; Yu Li; Chunyanx Zhang; Lingxuan Zhu; Weiming Mou; Zaoqu Liu; Jian Zhang; Quan Cheng; Ting Wei; Peng Luo (Gut Microbes)
The integration of fecal microbiota transplantation (FMT) with immune checkpoint inhibitors (ICIs) presents a promising approach for enhancing cancer treatment efficacy and overcoming therapeutic resistance. This review critically examines the controversial effects of FMT on ICIs outcomes and elucidates the underlying mechanisms. We investigate how FMT modulates gut microbiota composition, microbial metabolite profiles, and the tumor microenvironment, thereby influencing ICIs effectiveness. Key factors influencing FMT efficacy, including donor selection criteria, recipient characteristics, and administration protocols, are comprehensively discussed. The review delineates strategies for optimizing FMT formulations and systematically monitoring post-transplant microbiome dynamics. Through a comprehensive synthesis of evidence from clinical trials and preclinical studies, we elucidate the potential benefits and challenges of combining FMT with ICIs across diverse cancer types. While some studies report improved outcomes, others indicate no benefit or potential adverse effects, emphasizing the complexity of host-microbiome interactions in cancer immunotherapy. We outline critical research directions, encompassing the need for large-scale, multi-center randomized controlled trials, in-depth microbial ecology studies, and the integration of multi-omics approaches with artificial intelligence. Regulatory and ethical challenges are critically addressed, underscoring the imperative for standardized protocols and rigorous long-term safety assessments. This comprehensive review seeks to guide future research endeavors and clinical applications of FMT-ICIs combination therapy, with the potential to improve cancer patient outcomes while ensuring both safety and efficacy. As this rapidly evolving field advances, maintaining a judicious balance between openness to innovation and cautious scrutiny is crucial for realizing the full potential of microbiome modulation in cancer immunotherapy.